Pengaruh Corporate Social Responsibility Terhadap Accrual Quality Pada Sektor Industri Dasar dan Kimia Di Indonesia - Vonny Vinisia; Juniarti Juniarti (Business Accounting Review, 2016)
The affect of corporate social responsibility (CSR) on financial performance had been studied before, however there were only a few studies and had a mix finding between the affect of CSR on accrual quality. The aim of this research was to examine the affect of CSR on accrual quality in Chemical and basic Industry sector listed in Indonesia Stock Exchange (IDX).CSR was measured by GRI Index version 3.1, while accrual quality was measured by standard deviation of residual based on Dechow and Dichev’s model regression. The control variabels used in this research were firm size and leverage. 88 firm years during 2009-2013 were used as a sample in Chemical and Basic Industry sector listed on Indonesia Stock Exchange (IDX).The results indicated that independent variable CSR and control variable firm size and leverage had no influence on accrual quality.